Pengaruh Marketing Mix terhadap Customer Loyalty melalui Customer Satisfaction Kerudung di Outlet Rabbani - Fahrurrazi Fahrurrazi; Saila Khoirunnisa; Bambang Somantri (Institut Manajemen Wiyata Indonesia, 2019)
This study aims to determine the effect of brand image, product quality and price on customer loyalty through customer satisfaction products at Rabbani outlet Kota Sukabumi. The research method uses a survey method using a questionnaire distributed to 100 samples. The instrument quality testing techniques include validity and reliability tests. Data analysis techniques use descriptive analysis and correlation, while for hypothesis testing using path analysis. The first result on customer satisfaction shows that brand image has no direct effect on customer satisfaction, while product quality and price directly affect on customer satisfaction. The second result on customer loyalty shows that brand image, product quality and price directly had no effect on customer loyalty. This research is expected to help companies in applying the marketing mix that is adjusted to the conditions in the company environment so that it can be implemented.